Foetal alcohol spectrum disorder : mediating interventions through pregnant women's responses and choices - De Waal, Johanna Maria (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2010.